THE INFLUENCE OF KNOWLEDGE, TRAINING, MASTERY OF TECHNOLOGY ON PERFORMANCE IN LECTURERS - Khairuddin Nasution (Mount Hope Economic Global Journal, 2024)
The aim of this research is to Knowing the Big Influence Knowledge , Training , Mastery Technology Regarding the Performance of Lecturers. Research methods Study This set approach qualitative . Research result By Partial Knowledge influential positive and significant on Performance. Influence Training on Performance, then training influential positive and significant influence performance and personal selling positive and significant on Performance. Whereas in a way simultaneous Knowledge , Training and Mastery Technology influential positive and significant on Performance.